ENFORCEMENT OF THE DISCIPLINE REGULATIONS OF CIVIL SERVANTS SPECIFICALLY EDUCATORS IN THE EDUCATION, YOUTH AND SPORTS OFFICE OF KUDUS REGENCY BASED ON LAW NO. 43 OF 1999 ON STAFFING POINTS - Muhammad Fauzunnas (SEAN Institute, 2021)
Enforcement of Civil Servant Discipline Regulations at the Kudus Regency Education, Youth and Sports Office is an effort or effort made by the Kudus Regency Government, especially at the Kudus Regency Education, Youth and Sports Office in creating disciplined and quality civil servants, and providing services to the public because civil servants as government officials and public servants to serve the public interest are expected to always be ready to carry out the duties that have become their responsibilities properly. The problems studied in this study are: (1) How is the application of discipline for Civil Servants specifically for educators at the Education Office, Kudus Regency Youth and Sports? (2) What are the factors that influence the occurrence of violations of Civil Servants specifically for educators in the Office of Education, Youth and Sports of Kudus Regency? (3) What are the efforts that have been made by the Education, Youth and Sports Office of Kudus Regency in increasing the discipline of Civil Servants especially for Kudus Regency educators? This study aims to: (1) To determine the level of work discipline of Civil Servants especially educators in the Office of Education, Youth and Sports of Kudus Regency. (2) To find out the inhibiting factors in improving the discipline of Civil Servants, especially educators at the Kudus Regency Education, Youth and Sports Office. (3) To improve the performance of Civil Servants, especially educators in the Education Office, Kudus Regency Youth and Sports. This study uses a descriptive qualitative method, while the approach is a sociological juridical approach. The location of this research is the Office of the Education, Youth and Sports Office of the Kudus Regency. Sources of research data through: 1) Informants. 2) Respondents. For the informants are employees of the Education Office and the researchers interviewed 5 people and for the respondents were educators and the researchers interviewed 6 people. Data collection techniques are carried out through: 1) Interviews. 2) Observation 3) Documentation. The data is then selected and analyzed through 1) Data collection, 2) Data presentation, 3) Data verification. This study obtained the following results: (1) The number of educators who were affected by minor violations were 2 people, moderate disciplinary violations were 1 person